På spaning efter fritidspedagogisk undervisning - Dahl, Marianne (Nordisk Tidskrift för Allmän Didaktik, 2021)
The study aims at showing how teaching within school-age educare can be made visible through a LEGO project. Using Bernstein’s socio-linguistic theory, a re-analysis and a case-study are carried out. With a focus on how teachers teach, field notes from a previously conducted study are processed again. Results show that teaching within school-age educare is based on a visible pedagogy of both strong classification and framing, in line with a formal image of instruction. At certain times, the teaching becomes invisible, primarily from the children’s perspective, partly because of admonitions to maintain the project and partly because of the children’s sense of control whether project events are real or pretend. The play-oriented features and child focus in the project can be seen as a strategy, demonstrating opportunities of school-age educare teaching to create behavior that explores different knowledge. One conclusion highlights the teachers’ sense of intonation, an art requiring teachers to lead and participate in order to provide the conditions for learning. This teaching can complement the school.